Associations between partner's diet undermining and poor diet in mixed-weight, older gay married couples: a dyadic mediation model. Issue 10 (3rd October 2021) - Novak, Joshua R.; Wilson, Stephanie J.; Gast, Julie; Miyairi, Maya; Peak, Terry
Abstract: Background: Prior studies have examined how individuals may undermine their partner's efforts to maintain a healthy diet, but gay couples have not been represented in this work. Additionally, research has not accounted for mixed-weight status [lighter partner (LP) and heavier partner] nor investigated the mechanisms through which undermining is associated with dietary outcomes. Objective/Design/Measures: Utilising dyadic data from 224 gay married couples across the United States, we tested associations between perceptions of partner's diet undermining strategies and diet quality with couple food disagreements and depressive symptoms as putative, serial mediators in an actor-partner interdependence mediation model. Results: Results revealed that more severe diet undermining was associated with both partners' poorer diet quality, which was explained by more frequent couple food disagreements and higher depressive symptoms for both heavier and LPs. Conclusion: These findings suggest that undermining strategies are detrimental to both partners' relational health (increased conflict), emotional health (depressive symptoms) and physical health (diet)—regardless of weight status—and provide valuable targets for prevention and intervention. Our study underscores the interdependence of couple relations in lifestyle changes and specifically highlight the need for health professionals to discuss the partner's indirect or unintended disruptions to the patient's plan.